INTEGRATING ICT IN EFL CLASSROOM - Putri Meldia; Supratman Zakir (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
The purpose of this study is to examine the difficulties teachers face in integrating ICT into the teaching and learning English at Islamic Junior High School. As an example, learning innovations that use ICT are no longer in phase 4.0, but are now in phase 5.0, which means that ICT is being used in all fields. Following these advancements, the integration of ICT in education has become a necessity in today's world. As a result, this fact necessitates that teachers be capable of using ICT in the classroom. However, in the field, researchers discovered a number of barriers to teachers' use of ICT in the classroom. This study takes a qualitative approach: case study. This researh focuses on observations and interviews with one English teacher in order to obtain more detailed results. This study's informant is an English teacher. The lack of training on integrating ICT into the teaching and learning process of English in the classroom, competencies, equipment, computer support, time management, and technical skills were all identified as barriers to English teachers integrating ICT. The results suggest that teachers encounter difficulties and barriers when attempting to integrate ICT into the classroom's English teaching and learning process.